Diving into the Depths of Belladonna: Uncovering the Secrets of the Deadly Nightshade - Nikandish, Mehrasa (European Scientific Journal, ESJ, 2024)
Tropane alkaloids, such as hyoscyamine and scopolamine, are vital medicinal compounds found in various therapeutic formulations. These alkaloids are synthesized within the roots of specific genera of the Solanaceae family through a complex, partially understood multistep pathway. In efforts to deepen our comprehension of tropane alkaloid biosynthesis, a novel de novo transcriptome assembly was crafted for Deadly Nightshade (Atropa belladonna). A crucial intermediate in the biosynthesis of hyoscyamine and scopolamine is littorine, formed by the condensation of tropine and phenyllactic acid. Phenyllactic acid originates from phenylalanine through transamination to phenylpyruvate. Through transcriptome analysis, a distinct aromatic amino acid aminotransferase (ArAT), designated Ab-ArAT4, was identified. This enzyme coexists with known tropane alkaloid biosynthesis genes in the roots of A. belladonna. Silencing Ab-ArAT4 resulted in diminished synthesis of hyoscyamine and scopolamine due to reduced phenyllactic acid levels. In vitro studies revealed that recombinant Ab-ArAT4 primarily catalyzes the initial step of phenyllactic acid synthesis: the transamination of phenylalanine to phenylpyruvate.